PENGARUH INSENTIF DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PABRIK KELAPA SAWIT 1 PADA PT PERKEBUNAN MITRA OGAN BATURAJA - Yopi Yunsepa; Joni Joni (STIE DWI SAKTI BATURAJA, 2017)
This study aims to determine the effect of incentives and organizational culture on the performance of employees of Palm Oil Factory 1 at PT Perkebunan Mitra Ogan Baturaja. The research was conducted at PT Perkebunan Mitra Ogan Baturaja. The number of respondents were 93 employees in this study. Data collection was done through interview, observation and spreading of the questionnaire. The analysis technique used is multiple linear regression. The results showed that the incentives and organizational culture partially and simultaneously affect the performance of employees of Palm Oil Factory 1 at PT Perkebunan Mitra Ogan Baturaja.